2003
DOI: 10.1016/j.str.2003.08.012
|View full text |Cite
|
Sign up to set email alerts
|

The Atomic Structure of Rice dwarf Virus Reveals the Self-Assembly Mechanism of Component Proteins

Abstract: Rice dwarf virus (RDV), the causal agent of rice dwarf disease, is a member of the genus Phytoreovirus in the family Reoviridae. RDV is a double-shelled virus with a molecular mass of approximately 70 million Dalton. This virus is widely prevalent and is one of the viruses that cause the most economic damage in many Asian countries. The atomic structure of RDV was determined at 3.5 A resolution by X-ray crystallography. The double-shelled structure consists of two different proteins, the core protein P3 and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
162
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 142 publications
(172 citation statements)
references
References 31 publications
10
162
0
Order By: Relevance
“…2A). The organization of VP1A and VP1B in the capsid shell is identical to that of other reoviruses analyzed by X-ray crystallography or cryo-EM (2,8,9,(18)(19)(20)(21). A previous structural study by Yu et al has shown that the capsid shell protein VP1 has an overall thin-plate-like shape similar to that of orthoreovirus λ1 with the exception of a small protrusion domain (6).…”
supporting
confidence: 53%
“…2A). The organization of VP1A and VP1B in the capsid shell is identical to that of other reoviruses analyzed by X-ray crystallography or cryo-EM (2,8,9,(18)(19)(20)(21). A previous structural study by Yu et al has shown that the capsid shell protein VP1 has an overall thin-plate-like shape similar to that of orthoreovirus λ1 with the exception of a small protrusion domain (6).…”
supporting
confidence: 53%
“…The genome is composed of 12 double-stranded RNA segments. The structure of RDV has been solved by cryo-EM (Zhou et al, 2001) and X-ray crystallography (Nakagawa et al, 2003). In this study, RDV was used as the test case to validate the algorithm development.…”
Section: Resultsmentioning
confidence: 99%
“…The resolutions of the 3-D reconstructed maps were measured against the known X-ray structure (PDB ID: 1UF2) (Nakagawa et al, 2003) using the 0.5 criterion in the Fourier Shell Correlation (FSC) (Harauz and van Heel 1986) curves. The secondary structure elements were identified computationally by SSEHunter and visualized with Chimera (Pettersen et al, 2004).…”
Section: Cryo-em Images Of Rdvmentioning
confidence: 99%
“…For the more highly segmented Reoviridae, a model similarly based on specific RNA-protein interactions may be considered unlikely as it would require up to 11 distinct intermediate binding specificities to be generated in the capsid. There is no evidence that such structurally distinct capsid variants exist amongst the known capsid structures of this family (Grimes et al, 1998;Lawton et al, 1997;Mindich, 1999;Nakagawa et al, 2003;Pesavento et al, 2006;Reinisch et al, 2000). Additionally, the highly reiterative nature of the structural proteins which define the architecture of the virus particle argues that they would be poor candidates for providing a unique copy of a binding site for each segment during genome packaging.…”
Section: Introductionmentioning
confidence: 99%